Interpreting the dynamic performance effect of intellectual capital through a value-added-based perspective - Irene, Wei Kiong Ting; Chunya, Ren; Fu-Chiang, Chen; Qian, Long Kweh (Emerald Publishing Limited, 2020)
Purpose The question of whether intellectual capital (IC) is beneficial to firm performance is debatable because of the diverse effects of IC and its components on firm performance. Building on the concept of pay–performance relation, this study aims to provide new insights into how changes in IC affect changes in firm performance.